Age structural impact of adolescent and youth on fertility transition in Nepal - Pokharel, Trilochan (Nepal Population Journal, 2018)
Nepal is in unique period of demographic situation. The age structure of population is gradually shifting upwards producing a historical large proportion of young population. Given the early age at marriage and childbearing, this population may continue to dominate fertility transition process. Interaction between improvement in the characteristics of this population and recently started declining fertility is expected to push fertility transition at a faster rate until mid of this century before entering to the lowest level marginal decline or stagnation. The young 1population itself are in social, economic, cultural and demographic transition which is sandwiched with generation gap. Demographic analysis should factor their needs and interests to project the future fertility discourse.